SYNCHROMODAL LOGISTICS NETWORKS: SYNCHROMODAL LOGISTICS NETWORKS - Rahnev, Mariyan (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The intermodal freight transportation is being discussed for decades as an alternative to the unimodal automobile transportation. However, it is still not a significant part of the total market of the freight transportation. A new and promising possibility for improvement the efficiency of the freight transportation systems is the synchromodal design of the transportation systems on the inside. A cornerstone for the synchromodality is the integrated view in the design and functioning of the intramodal transportation. With the synchromodal transportation we have a flexible and dynamic way of choosing the best transportation. Synchromodality can lead to a modal transition to a slower but more ecological ways of transport without compromising the cost or the quality. A prerequisite for synchromodal transportation is the ability to freely choose which transportation method to use and easily to switch from one method to another.